Alocação de zeros aplicada a sistemas de controle via LMI - Assunção, Edvaldo [UNESP]; Andrea, Cristiano Quevedo [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP] (FapUNIFESP (SciELO), 2007)
A systematic procedure of zero placement to design control systems is proposed. A state feedback controller with vector gain K is used to perform the pole placement. An estimator with vector gain L is also designed for output feedback control. A new systematic method of zero assignment to reduce the effect of the undesirable poles of the plant and also to increase the velocity error constant is presented. The methodology places the zeros in a specific region and it is based on Linear Matrix Inequalities (LMIs) framework, which is a new approach to solve this problem. Three examples illustrate the effectiveness of the proposed method.
Keywords: Control systems; LMI; Zeros placement; Control system analysis; Feedback control; Linear matrix inequalities; Problem solving; Vector quantization; State feedback controllers; Vector gain; State feedback